BANK INTERNAL FACTORS AND PROFIT DISTRIBUTION MANAGEMENT OF SYARIAH BANKS IN INDONESIA - Mismiwati, Mismiwati (Universitas Islam Negeri Raden Fatah Palembang, 2018)
AbstractThe purpose of this study is to analyze the effect of Capital Adequacy Ratio (CAR), Operation Efficiency (BOPO), Financing to Deposit Ratio (FDR), Proportion of Depositor’s Funding (PDPK), Purchase Financing (PJB), Profit Sharing Financing (PBH) and Return On Assets (ROA) to Profit Distribution Management (PDM) in Islamic banks in Indonesia. The sample determined by using purposive sampling based on Indonesia Syariah Bank for period of 2009-2013. The population in this research is 11 Syariah Banks, which 5 Syariah Banks are chosen based on purposive sampling. For analysis the data, multiple regression analysis with IBM SPSS. The result of the research shown that internal bank factors (BOPO and PBH) give positive effect to PDM, the internal bank factors (FDR and PDPK) give negative effect to PDM, while internal bank factors (CAR and PJB) do not affect to PDM. ROA gives positive effect on PDM. Keywords : CAR, BOPO, FDR, PDPK, PJB, PBH, ROA, PDM.